Usability and Users’ Satisfaction on Online Electronic Voting System / Adib Sarkawi ... [et al.] - Sarkawi, Adib; Johari, Aiza; Bujang, Azlina; Haji Bibi, Zainon (Universiti Teknologi MARA Cawangan Sarawak, 2021)
This paper identifies the respondents’ views towards e-Voting (electronic technology voting) such as the process, users’ satisfaction, and relevancy, and to determine the usability criteria of e- voting’s interface, in which it employs a quantitative method, using self-administered adapted questionnaires. The survey involves 250 respondents (voters), who immediately completed five Likert scales survey after they had voted for the committee members in two general elections: a social club for the university’s staff (using Internet) and an organization for the female staff of the university (using the Intranet). The respondents were of different demographic backgrounds and they casted their online votes at two different periods (two years difference). The data were analysed using the SPSS software. The study found positive responses from most of the voters in which they expressed their satisfaction that e-Voting was convenient and easy to be used in the voting process, where the system illustrated relevant content and generated adequate procedures. Notably, the usability criteria of the interface of e-Voting as indicated by most respondents are between good to very good scales (navigation, graphic, user-friendliness and consistency, content, and transparency).